Effect of hot air inclined jet impingement to container for controlling of energy storage of PCM: experimental and numerical investigation - Öztop, Hakan Fehmi; Kiyak, Burak; Aksoy, Ishak Gokhan (Emerald Group Publishing Ltd, 2025)
PurposeThis study aims to focus on understanding how different jet angles and Reynolds numbers influence the phase change materials' (PCMs) melting process and their capacity to store energy. This approach is intended to offer novel insights into enhancing thermal energy storage systems, particularly for applications where heat transfer efficiency and energy storage are critical.Design/methodology/approachThe research involved an experimental and numerical analysis of PCM with a melting temperature range of 22 degrees C-26 degrees C under various conditions. Three different jet angles (45 degrees, 90 degrees and 135 degrees) and two container angles (45 degrees and 90 degrees) were tested. Additionally, two different Reynolds numbers (2,235 and 4,470) were used to explore the effects of jet outlet velocities on PCM melting behaviour. The study used a circular container and analysed the melting process using the hot air inclined jet impingement (HAIJI) method.FindingsThe obtained results showed that the average temperature for the last time step at CYRILLIC CAPITAL LETTER EF = 90 degrees and Re = 4,470 is 6.26% higher for CYRILLIC CAPITAL LETTER EF = 135 degrees and 14.23% higher for CYRILLIC CAPITAL LETTER EF = 90 degrees compared with the 45 degrees jet angle. It is also observed that the jet angle, especially for CYRILLIC CAPITAL LETTER EF = 90 degrees, is a much more important factor in energy storage than the Reynolds number. In other words, the jet angle can be used as a passive control parameter for energy storage.Originality/valueThis study offers a novel perspective on the effective storage of waste heat transferred with air, such as exhaust gases. It provides valuable insights into the role of jet inclination angles and Reynolds numbers in optimizing the melting and energy storage performance of PCMs, which can be crucial for enhancing the efficiency of thermal energy storage systems.
Keywords: Phase change material; Thermal energy storage; Inclination angle; Hot air jet; Jet angle; Melting